Kartagener syndrome: Case report. (International Journal of Medical and Surgical Sciences, 2017)
Kartagener’s syndrome is an autosomal recessive disease, characterized by primary ciliary dyskinesia, which consists of ciliated cell dysfunction. This is the cause of the manifestation of the respiratory symptomatology that presents this syndrome-cough, sinusitis, and bronchiectasis. Another symptomatology that accompanies this syndrome are infertility and situs inversus. Its recognition from the early XX century, and constitutes syndrome thanks to the description of 4 clinical cases by Manes Kartagener, a pulmonologist who worked in Zurich and first described the triad of sinusitis, bronchiectasis and situs inversus in 1933. A 35-year-old female patient with a history of dextrocardia, repeated respiratory infections, and inadequate response to previous treatments, is presented to the Emergency Hospital Mario Catarino Rivas. Kartagener syndrome characterized by the classic triad of chronic sinusitis, bronchiectasis and situs inversus. During clinical presentation expect to find recurring upper and lower respiratory tract, thanks to the commitment of mobility infections ciliciar normally responsible for the removal of environmental pathogens, expected long-term development of bronchial dilation because of accumulation of mucoid material and local inflammatory reaction.